Effect of Fibre Volume Fraction and Sodium Hydroxide Treatment on Mechanical Properties of Palm Fibre/Unsaturated Polyester Composite - Tri Partuti; Umar Hamzah Fariyan; Yanyan Dwiyanti; Adhitya Trenggono; Erlina Yustanti (Universitas Negeri Malang, 2022)
Wood has some weaknesses, such as susceptibility to weathering, easily attacked by termites, and low water resistance. An alternative material such as Natural Fibre-Reinforced Polymer (NFRP) composite should overcome those weaknesses. This research aims to make a composite with palm fibre and unsaturated polyester resin. Palm fibres immerse for 2 hours in NaOH solution with varying concentrations of 3%, 5%, and 7%. The volume fraction of palm fibre are 0%, 5%, 10%, 15%, and 20%. Woven roving fibreglass was added to compare the tensile strength of composite with or without natural fibre. The density of composites increased with the increase of fibre volume fraction. The highest tensile strength was obtained for 15% of fibre volume fraction, namely 23.8483 MPa. In contrast, the highest compressive strength was obtained for 5% of fibre volume fraction, namely 94.76 MPa. NaOH removed the impurities and waxy substances from the fibre surface and created a rougher surface topography after alkalization. The highest tensile strength was obtained with 7% NaOH, namely 14.674 MPa. The highest water absorption value was obtained at 3% NaOH concentration and 15% of fibre volume fraction, namely 1.445%. The addition of woven roving as reinforcement to natural fibre composite can increase tensile strength by 210%, from 13.882 MPa to 43.123 MPa.DOI: 10.17977/um024v7i12022p039